2019
DOI: 10.1139/cgj-2018-0387
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of nanoscale zero-valent iron (nZVI) on the mechanical properties of lead-contaminated clay

Abstract: Nanoscale zero-valent iron (nZVI) is a well-known efficient nanomaterial for the immobilization of heavy metals and has been widely applied in the remediation of contaminated groundwater and soils. In this study, a series of field emission scanning electron microscopy (FESEM) analyses, vane shear tests, triaxial compression tests, and oedometer tests was conducted on lead-contaminated clay using four dosages of nZVI treatment (0.2%, 1%, 5%, and 10%). The geotechnical properties, including basic index propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Various dosages, such as 0.2%, 0.5%, 1%, 2%, and 5% (dry soil weight), of nZVI particles were added into the contaminated slurry under ultrasonic and stirring conditions. After following the recommended mixing reaction time of 10 min, it could achieve a full dispersion and reactions of nZVI in the soil slurry, which has been proven by the literature [31,37,43,44]. Then, the treated slurry was transferred to a double-drainage tank for a preconsolidation process with effective vertical stress of approximately 100 kPa, which was confirmed through Casagrande's method in trial oedometer tests.…”
Section: Preparation Of Soil Samplesmentioning
confidence: 75%
See 1 more Smart Citation
“…Various dosages, such as 0.2%, 0.5%, 1%, 2%, and 5% (dry soil weight), of nZVI particles were added into the contaminated slurry under ultrasonic and stirring conditions. After following the recommended mixing reaction time of 10 min, it could achieve a full dispersion and reactions of nZVI in the soil slurry, which has been proven by the literature [31,37,43,44]. Then, the treated slurry was transferred to a double-drainage tank for a preconsolidation process with effective vertical stress of approximately 100 kPa, which was confirmed through Casagrande's method in trial oedometer tests.…”
Section: Preparation Of Soil Samplesmentioning
confidence: 75%
“…The introduction of nZVI has been found to alter the microstructure of contaminated soil, subsequently impacting its deformation characteristics and then affecting the reuse of treated sites. When an appropriate or excessive amount of nZVI is used for degrading Pb(II) in the soil, the products generated tend to precipitate on the surfaces of soil particles, forming large aggregates and dense connection structures, resulting in reduced soil porosity and expansion index [31]. Soil permeability can also serve as a measure of deformation characteristics [32].…”
Section: Introductionmentioning
confidence: 99%
“…A laboratory application demonstrated that contaminated soil with 400 mg/kg of Pb(II) treated with nZVI increased its undrained shear strength from 25.83 kPa (with 0.2% nZVI) to 69.33 kPa (with 10% nZVI) [36]. It was reported that, after 5% nZVI treatment, the internal friction angle of the contaminated soil increased from 21.5 • (contaminated soil) to 28.2 • (5% nZVI treated soil), and the increasing moduli of treated soil was also observed [37]. Nasehi et al [38] also noted improvements in Unconfined Compressive Strength (UCS) and undrained shear strength in diesel-contaminated soils after nZVI application.…”
Section: Introductionmentioning
confidence: 94%
“…The physical technology includes surcharge loading, pile installation, deep compaction (Wang and Chen 2019;Wang et al 2019aWang et al , 2019bZhao et al 2019;Chen et al 2020), etc., normally consuming substantial energy resources, and causing soil disturbance and noise in the vicinity. The chemical grouting comprises of the treatment with lime, cement, fly ash (Yin and Zhou 2009;Yuan et al 2016;Shen et al 2017;Chen et al 2019b), etc., which is chemically toxic and environmentally contaminating. Considering the limitations of the current technologies used for soil improvement, a new sustainable, efficient, economic and environmentally friendly approach is needed.…”
Section: Introductionmentioning
confidence: 99%